PERAN KPU KOTA TANGERANG DALAM MEMBANGUN BUDAYAPOLITIK MASYARAKAT UNTUK MENINGKATKAN PARTISIPASIPOLITIK PADA PILPRES 2019 - Ririn Afrizka (2022)
This study aims to find out how the role played by the KPU Tangerang City in Building Community Political Culture to Increase Political Participation in the 2019 Presidential Election. By using role theory, political socialization theory and political participation theory and the concept of political culture. The research method used in this study is a qualitative research method using primary data and secondary data. Data collection techniques are interviews, literature studies, and documentation. Researchers used three stages of data analysis, namely data reduction, data presentation, and drawing conclusions. The results of this study found that the role played by the KPU Tangerang City in building a political culture to increase public political participation in the 2019 presidential election was to carry out Political Socialization and Voter Education activities. This socialization activity is carried out by direct and indirect methods or face-to-face. Direct socialization activities include: Election Course, KPU Goes to School, Cultural Arts Performance, Family-Based Socialization, Dissemination to Disabilities, Voter Creative Socialization, and Democracy Volunteers. Then, indirect socialization is socialization using electronic media such as TV and radio, while online media using Twitter, Instagram, Website, Facebook, Youtube.